Jean Stanislas Mittié et la syphilis - Beaulieu, Léonie (Université de Montréal, 2021)
Jean-Stanislas Mittié, a medical doctor from the Paris region, develops and attempts to gain approval for a vegetal cure to syphilis between 1777 and 1795. The present memoir proposes an analysis of the various textual documents surrounding his endeavours in order to assess the impact of the end of the Ancien Régime and the French Revolution on his medical practice. His individual story reveals the important transformations of institutional, political and cultural power structures regulating medicine at the end of the 18th century.
Keywords: French revolution; History - European / Histoire - Européenne (UMI : 0335); Jean-Stanislas Mittié; Medicine; Révolution française; médecine; syphilis